2023
DOI: 10.3390/rs15194655
|View full text |Cite
|
Sign up to set email alerts
|

Water Area Extraction and Water Level Prediction of Dongting Lake Based on Sentinel-1 Dual-Polarization Data Decomposition

Qing Song,
Rong Zhao,
Haiqiang Fu
et al.

Abstract: The Sentinel-1 imaging radar mission provides a short revisit-time, continuous all-weather, and day-and-night imagery at the C-band, which brings opportunities for the dynamic extraction of lake water areas. For wetland-type lakes, it is difficult to distinguish between the water, submerged plants, and mudflats at the edge of a lake, which leads to difficulty in recognizing the water edge of a lake and affects the accuracy of lake water area extraction. In this paper, a water area extraction and water level pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…This implies that the variation rates of water area in Dongting Lake can be unsteady and different from those of water level and water flow at Chenglingji station at different scales. Compared with previous studies with relatively high model fitting R 2 values for level-area correlations (>0.9) [24,26], the accuracy at the seasonal scale is acceptable, while that at the annual and monthly scales is relatively low. This is probably because (1) unlike previous studies that mainly focused on the East Dongting Lake area directly related to the Chenglingji hydrological station, this study is based on the entire Dongting Lake area and includes parts such as South Dongting Lake and West Dongting Lake; (2) this model of water level-area and water flow-correlations for the study period from 2000 to 2021 at annual, seasonal, and monthly scales, the average process of area, level and flow will smooth the data variation and make correlations more rough compared to studies based on daily water area and water level data; (3) the limited number of samples at the annual scale may influence the performance and representativeness of models; (4) the relatively high uncertainty in water area at the monthly scale can conceal the correlations to some extent.…”
Section: Water Level-area Flow-area and River-lake Correlationscontrasting
confidence: 65%
See 2 more Smart Citations
“…This implies that the variation rates of water area in Dongting Lake can be unsteady and different from those of water level and water flow at Chenglingji station at different scales. Compared with previous studies with relatively high model fitting R 2 values for level-area correlations (>0.9) [24,26], the accuracy at the seasonal scale is acceptable, while that at the annual and monthly scales is relatively low. This is probably because (1) unlike previous studies that mainly focused on the East Dongting Lake area directly related to the Chenglingji hydrological station, this study is based on the entire Dongting Lake area and includes parts such as South Dongting Lake and West Dongting Lake; (2) this model of water level-area and water flow-correlations for the study period from 2000 to 2021 at annual, seasonal, and monthly scales, the average process of area, level and flow will smooth the data variation and make correlations more rough compared to studies based on daily water area and water level data; (3) the limited number of samples at the annual scale may influence the performance and representativeness of models; (4) the relatively high uncertainty in water area at the monthly scale can conceal the correlations to some extent.…”
Section: Water Level-area Flow-area and River-lake Correlationscontrasting
confidence: 65%
“…These characteristics may be ignored by studies based on traditional time series analysis methods at a single temporal scale. Some studies have established a fitting model between satellite-derived water area and hydrological monitoring data to explore the relationships between rivers and lakes and to simulate changes in water area [23][24][25][26]. They could reveal the characteristics of the relationship to some extent, but similar to the analysis of lake water area, they usually analyzed at a single scale and established a unified relationship model between hydrological indicators (mainly water level) and area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This comprehensive data collection approach ensures that the study is underpinned by a wealth of information spanning multiple domains, providing a holistic understanding of the Khinjhir Lake wetland and the various factors affecting it [50,51].…”
Section: Data Collectionmentioning
confidence: 99%
“…There are still some wetlands around the world that are not internationally recognized, and studies have shown that remote sensing technology is able to define wetlands [4]. At the same time, after extracting the area of wetlands, it is possible to estimate GHG emissions, which is of great significance for the prevention of global warming [5]. The Zhalong Wetland is a typical inland alkaline wetland ecosystem in Northern China, with an area of about 2100 km 2 , with vegetation types mainly dominated by Phragmites australis [6].…”
Section: Introductionmentioning
confidence: 99%